2022
DOI: 10.3390/women3010002
|View full text |Cite
|
Sign up to set email alerts
|

“We Beat Them to Help Them Push”: Midwives’ Perceptions on Obstetric Violence in the Ashante and Western Regions of Ghana

Abstract: Obstetric violence has been recognized as a major impediment to facility-based delivery, increasing the risk of preventable complications and maternal mortality. In Ghana, studies on women’s birth experiences reveal enormous and brutal acts of violence during delivery; however, inquiries into why midwives abuse women have not been extensively studied. This study explored the perspectives of midwives on the drivers of obstetric violence in the Western and Ashante Regions of Ghana. A qualitative study was conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Furthermore, our study also found that single women were about 60% more likely than married women to be abused during childbirth, revealing how gender constructions of marriage shape women's treatment. Marriage is considered a symbol of responsibility, honor and a prestigious identity for Ghanaian women ( 46 ), earning married women more respect in society with single mothers being perceived as irresponsible and somewhat sexually immoral. Our finding is consistent with Bohren et al ( 31 ) study on mistreatment during childbirth in Ghana, Guinea, Myanmar and Nigeria, where abuse was much higher among single mothers than married women.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study also found that single women were about 60% more likely than married women to be abused during childbirth, revealing how gender constructions of marriage shape women's treatment. Marriage is considered a symbol of responsibility, honor and a prestigious identity for Ghanaian women ( 46 ), earning married women more respect in society with single mothers being perceived as irresponsible and somewhat sexually immoral. Our finding is consistent with Bohren et al ( 31 ) study on mistreatment during childbirth in Ghana, Guinea, Myanmar and Nigeria, where abuse was much higher among single mothers than married women.…”
Section: Discussionmentioning
confidence: 99%
“…Obstetric violence as a concept is relatively new in the global health literature with researchers adopting various terminologies such as ‘disrespect and abuse (D&A),’ ‘mistreatment and abuse,’ ‘dehumanized childbirth,’ and ‘disrespectful maternity care’ to describe violence and abuse in obstetric care. While these terminologies help to clearly categorize the different manifestations of violence, the term ‘obstetric violence’ emphasizes the ‘structural dimensions as a gender-based violence that intersects with institutional violence’ ( 3 , 4 ). Nonetheless, all the terminologies acknowledge the harmful effects of violence, the dehumanization of childbirth and the violation of women’s rights and dignity.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we use the term ‘obstetric violence’ interchangeably with the other terminologies to cover vast literature. Obstetric violence could manifest in the form of physical violence, denial of birth companion, intimidation, forced medical care, neglect or abandonment, lack of confidentiality, failure to seek consent, unjustified cesarean sections, restrictions on food and mobility, and excessive use of oxytocin to induce labor ( 3 , 5–7 ). Women are often stripped of the agency to make decisions over their bodies, while some are subjected to dehumanizing treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prevalence figures vary largely in different countries [ 1 , 23 , 24 , 25 ]. Reported prevalence rates of mistreatment or abuse of women during labor range from 11% in Mexico [ 26 ] and 49.4% in Latin America [ 27 ] to more than 70% in some African countries [ 28 , 29 , 30 ]. High OV prevalence rates have also been reported in Europe [ 1 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%